Structure and species composition of diatom community during the wet season in three floodplain lakes of Brazilian Pantanal. - Margaret S Nardelli; Denise C Bicudo; Silvio C Sampaio; Cláudia M D S Cordovil (PLoS ONE)
In order to access environmental conditions, the use of bioindicators that have a close relationship with environmental stressors is a largely common practice, but when evaluating environmental inferences, the individual dominant taxa need to be interpreted. Humid regions such as the marshlands are fragile ecosystems and sustain communities of microalgae, often used as bioindicators, of which diatoms are a good example. Although they provide an excellent response to chemical and physical changes in water, diatom studies in surface sediments in wetlands are scarce worldwide. To determine whether diatom species have the potential to provide unambiguous inferences in the influence of environmental factors, we have evaluated diatom abundance in surface sediment, from three Pantanal lakes, against a set of environmental gradients: pH, dissolved oxygen, turbidity, conductivity, total dissolved solids, water temperature, index of trophic water status, total phosphorus and total nitrogen. The Ferradura lake presented an oligotrophic state and both Burro and Caracará lakes presented mesotrophic state. Diatoms were more abundant in the a mesotrophic conditions, but with higher species richness in the oligotrophic conditions. Depending on the N:P ratio, the nutrients nitrogen and phosphorus can also play the role of pollutants and may have negative and unpredictable effects in the environment, such as biotic homogenization. Despite the spatial variation in species, there was a greater richness of Eunotia Ehrenberg species, with the highest relative density of Eunotia formica Ehrenberg and E. pantropica Glushchenko, Kulikovskiy & Kociolek, due to the environmental acidic conditions, a determining characteristic of this genus. It was also observed that a small increase in the level of phosphorus generated an increase in the abundance of Aulacoseira Thwaites with the highest relative density of A. pusilla (Meister) Tuji & Houki and A. veraluciae Tremarin, Torgan & T.Ludwig. However, A. italica dominated in the moderately acidic environment. The results can help with decisions in impacted areas to solve socioeconomic problems, environmental management and biodiversity.